How do maternal interaction style and joint attention relate to language development in infants with Down syndrome and typically developing infants?. (December 2018) - Seager, Emily; Mason-Apps, Emily; Stojanovik, Vesna; Norbury, Courtenay; Bozicevic, Laura; Murray, Lynne
Highlights: Responding to joint attention is positively related to concurrent language in infants with DS aged 17–23 months. Maternal interactive style is positively related to language in TD infants of equivalent non-verbal mental age. Different social communication factors concurrently predict language in TD infants and infants with DS. Abstract: Down syndrome (DS) is more detrimental to language acquisition compared to other forms of learning disability. It has been shown that early social communication skills are important for language acquisition in the typical population; however few studies have examined the relationship between early social communication and language in DS. The aim of the current study is to compare the relationship between joint attention and concurrent language skills, and maternal interactive style and concurrent language skills in infants with DS and in typically developing (TD) infants matched for mental age. We also investigated if these relationships differ between children with DS and TD children. Twenty-five infants with DS (17–23 months) and 30 TD infants (9–11 months) were assessed on measures of joint attention, maternal interactive style and language. The results indicated a significant positive relationship between responding to joint attention (RJA) and concurrent language for the DS group, and a significant positive relationship between maternal positive expressed emotion (PEEM) and concurrent language for the TD group. We hypothesise that different social-communication factors are associated with language skills in DS, at least between 17 and 23 months of age compared to TD infants of similar non-verbal and general language abilities.